Damping and cushioning characteristics of Polyjet 3D printed photopolymer with Kelvin model. (July 2021) - Ge, Changfeng; Cormier, Denis; Rice, Brian
This study extends previous research on the measurement of a 3D printed photopolymer's quasi-static cushion properties, to include cushion and damping properties due to impact loading. In order to develop analytical packaging models of 3D printed materials, it is essential to know how energy induced by shipping and handling is dissipated through damping. Compared to the cushion curve, investigating how damping influences packaging design is relatively unfamiliar to the packaging practitioner. This study uses experimentally derived hysteresis loops, from platen impact and quasi-static compression tests, to estimate specific damping capacities for 3D printed photopolymer. This study found that the "sticky" rubber like 3D printed photopolymers, based on a repeating pattern of Kelvin cells, were able to dissipate close to 100% of the input energy in platen impact tests and still return to their original dimensions after impact. In addition, this study shows that the specific damping capacity of the 3D printed structure increases significantly with strain rate.